Understanding trophic structure variation in fish assemblages of subtropical shallow lakes: Combined effects of ecosystem size, productivity, and disturbance - Yintao Jia (Elsevier, 2021)
Global environmental change has altered biotic interactions in ecosystems. Trophic structure is a major characteristic of ecosystems, and understanding the factors determining trophic structure is thus important for predicting the response of ecological dynamics and ecosystem services to future environmental change. Different kinds of drivers, including ecosystem size, productivity, and disturbance, have been proposed to explain trophic structure variation in various ecosystems. Much remains unknown about how these drivers operate in determining trophic structure and its underlying mechanisms, particularly in shallow lakes. Here, we evaluated the relative importance of ecosystem size, productivity and disturbance in influencing the trophic structure of fish assemblages in 30 subtropical shallow lakes. We determined that (1) ecosystem size, productivity and disturbance had no effect on food chain length; (2) the mean trophic level increased with increasing ecosystem size and productivity, with productivity contributing the most to explaining the variance in mean trophic level; and (3) ecosystem size, productivity, and disturbance, alone or combined, affected the proportion of species at specific trophic levels. These results indicate the potential for systematic discrepancies in the drivers of trophic structure among different systems and highlight that focusing on food chain length alone may not be sufficient in reflecting the variation in trophic status. Thus, changes in the mean trophic level and specific trophic-level guilds must be considered in future lake management practices.